The Role of CD103+ Dendritic Cells in the Intestinal Mucosal Immune System - Ruane, Darren T.; Lavelle, Ed C. (Frontiers in Immunology, 2011)
While dendritic cells (DC) are central to the induction and regulation of adaptive immunity, these cells are very heterogenous and specific subsets can be characterized based on the expression of cell surface markers and functional properties. Intestinal CD103+ DCs are the subject of particular interest due to their role in regulating mucosal immunity. Since the epithelial surfaces are constantly exposed to a high antigenic load, tight regulation of innate and adaptive intestinal immune responses is vital as intestinal inflammation can have detrimental consequences for the host. Strategically positioned within the lamina propria, CD103+ DCs play an important role in maintaining intestinal immune homeostasis. These cells are required for the induction of tolerogenic immune responses and imprinting gut homing phenotypic changes on antigen-specific T cells. Recent insights into their development and regulatory properties have revealed additional immunoregulatory roles and further highlighted their importance for intestinal immunity. In this review we discuss the nature of the intestinal CD103+ DC population and the emerging roles of these cells in the regulation of mucosal immunity.